2015
DOI: 10.1055/s-0035-1553359
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Brain Imaging in Isolated vs. Complicated Club Foot: A Cohort Study

Abstract: Talipes equinovarus (TEV) is a common birth defect. Differentiation between isolated and complex TEV is fundamental due to its effect on prognosis. Association between TEV and poor neurological outcome is more prominent in complex cases and highlights the significance of brain evaluation. The aim of the current study was to evaluate the contribution of fetal brain MRI to sonographic evaluation. In this retrospective study we evaluated charts of all pregnant patients referred for fetal brain MRI due to fetal TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In all, 778 articles were identified; 46 were assessed for eligibility for inclusion and 25 studies were included in the systematic review (Table , Figure , see Supplementary material, Table , Figure ) . These 25 studies included 1567 fetuses affected by isolated talipes on ultrasound, defined as the presence of talipes with no associated anomalies at the time of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 778 articles were identified; 46 were assessed for eligibility for inclusion and 25 studies were included in the systematic review (Table , Figure , see Supplementary material, Table , Figure ) . These 25 studies included 1567 fetuses affected by isolated talipes on ultrasound, defined as the presence of talipes with no associated anomalies at the time of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (118 fetuses) explored the occurrence of associated anomalies detected only at a follow‐up examination in fetuses with a prenatal diagnosis of isolated talipes. Overall, associated anomalies not detected on ultrasound were detected in 7.8% (95% CI 0.1%‐29.3%) of cases at follow‐up ultrasound, whereas in 4.0% (95% CI 0.1%‐13.2%) of cases, fetal MRI detected anomalies that were not detected at ultrasound assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The final studies selected by the reviewers included the following levels of evidence: 19 level III retrospective studies [ 1 , 2 , 7 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 21 , 22 , 25 , 26 , 27 ], 3 level II prospective comparative studies [ 8 , 11 , 20 ], 1 descriptive study of level III [ 19 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six of the studies identified reported associated pathologies [ 9 , 14 , 21 , 24 , 25 , 27 ]. The following were mentioned in at least 1 of the studies included; Trisomies: 13, 18, 21, Neural Tube Defect, Skeletal Dysplasia, Cardiac anomalies, Sex Chromosome Abnormalities, Submicroscopic CNVs, Developmental Delay, Symptomatic Epilepsy, Thin corpus callosum, Visual inattentiveness, Peroneal Nerve Palsy, Low weight gain, Mild facial asymmetry, Delayed bone age, Cleft Palate, Finger Camptodactyly, Unusual facies, Cerebral Palsy, Rett Syndrome, Hypotonia, Coarse facial features, Torticollis, Hydramnios, Spina Bifida ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation